Supporting Adjunct Faculty - Sarah Edwards (Academic Chairpersons Conference Proceedings, 2019)
One of a chairperson’s many duties is to hire and support adjunct faculty. Helping adjuncts get to know campus policies, grow their instructional expertise and contribute to program assessments is a huge responsibility for a chairperson. Come hear practices that can support you as you work to support adjunct faculty.
Keywords: adjunct development; support systems; mentoring